1985
DOI: 10.21236/ada170751
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Near-Field and Teleseismic Observations of Seismic Source Parameters

Abstract: StCUMITY CLASSIP)CATION Or THIS PA;";-,x .ASSFI the Grafenberg array (6 to 13 stations) were averaged for each event and compare( to the single station (Al) results. Additionally, transverse component data were available for three of the GRF stations. At MAIO only vertical component Lg data were available. For the propagation path from Semipalatinsk to GRF, the narrow-band filtering method and the noise-corrected power spectra of both vertical and transverse components give an average Q for Lg of approximately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
(7 reference statements)
1
2
0
Order By: Relevance
“…There have been a number of studies which have indicated that measurements made in the P-coda are at least as stable as network-averaged m b estimates and significantly better than single-station m b (Baumgardt, 1983;Bullitt and Cormier, 1984;Baumgardt, 1984;Gupta et al, 1984). Similar results have been obtained for Lg and Lg-coda wave measurements (Ringdal, 1983;Alexander, 1984).…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…There have been a number of studies which have indicated that measurements made in the P-coda are at least as stable as network-averaged m b estimates and significantly better than single-station m b (Baumgardt, 1983;Bullitt and Cormier, 1984;Baumgardt, 1984;Gupta et al, 1984). Similar results have been obtained for Lg and Lg-coda wave measurements (Ringdal, 1983;Alexander, 1984).…”
Section: Introductionsupporting
confidence: 87%
“…In Table 3, the source parameters of the explosions in Table 2, including the tectonic components by Sykes and Cifuentes (1983) and Given et al (1983), are listed. As pointed out by Alexander (1984) Another important observation which can be drawn from these plots is that the slopes of the best fitting lines for the Lg measurements are quite small, ranging from 0.6 to 0.8. Interestingly, however, the P-coda measurements have higher slopes of 0.9 to 1.0.…”
Section: 2mentioning
confidence: 72%
See 1 more Smart Citation